2012
DOI: 10.1128/jvi.00270-12
|View full text |Cite
|
Sign up to set email alerts
|

RNase L Triggers Autophagy in Response to Viral Infections

Abstract: Autophagy is a programmed homeostatic response to diverse types of cellular stress that disposes of long-lived proteins, organelles, and invading microbes within double-membraned structures called autophagosomes. The 2=,5=-oligoadenylate/ RNase L system is a virus-activated host RNase pathway that disposes of or processes viral and cellular single-stranded RNAs. Here we report that activation of RNase L during viral infections induces autophagy. Accordingly, infections with encephalomyocarditis virus or vesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Addendum-While this work was under review, Chakrabarti et al (65) reported that RNase L triggers autophagy in response to viral infections, consistent with our data described here.…”
Section: Acknowledgmentssupporting
confidence: 88%
“…Addendum-While this work was under review, Chakrabarti et al (65) reported that RNase L triggers autophagy in response to viral infections, consistent with our data described here.…”
Section: Acknowledgmentssupporting
confidence: 88%
“…Herpes simplex virus type 1 can antagonize autophagy via the viral protein ICP34.5, and mice more easily clear ICP34.5-mutant viruses compared to wild type viruses, again suggesting a détente between autophagy and viruses [66]. More recent data suggest that autophagy can control other viruses such as human immunodeficiency virus (HIV), encephalomyocarditis virus and human papilloma virus in mammalian cells in certain contexts, although the in vivo significance has not been assessed [6769]. Since Drosophila are infected by viruses and are a genetically tractable model, flies are well suited for probing the interactions between viruses and autophagy.…”
Section: Restriction Of Viral Replication By Autophagymentioning
confidence: 99%
“…OVs such as Ad [54,79-81], HSV [70,82,83], reovirus [84-86], influenza virus [87], VSV and encephalomyocarditis virus [88] induce autophagy in cancer cells. Autophagy enhances tumor immunogenicity by two mechanisms.…”
Section: Introductionmentioning
confidence: 99%